A playback speech detection algorithm based on log inverse Mel-frequency spectral coefficient - Lang LIN; Rangding WANG; Diqun YAN; Can LI (Dianxin kexue)
The popularity and portability of high-fidelity audio recording equipment and playback equipment poses a serious challenge for speaker recognition systems against playback attacks.Based on the differences between the original speech and the playback speech in high frequency region,the algorithm reversed the Mel-filter bank in Mel-frequency cepstral coefficient (MFCC) calculation,and the coefficients before the DCT were used as the features of the algorithm.SVM was utilized as the classifier.Experimental results show that this algorithm can effectively detect the playback speech.In addition,the algorithm is integrated into the GMM-UBM speaker recognition system,which significantly improves the systems’ capability of resisting the playback attack.